Effect of dietary glycine and benzoate level on benzoate metabolism in mink (Mustela vison), blue fox (Alopex lagopus), and raccoon dog (Nyctereutes procyonoides) - Pölönen, Ilpo J.; Partanen, Kirsi; Jalava, Taina; Toivonen, Vesa (American society of animal science, 2000)
v ok